2011
DOI: 10.1634/theoncologist.2011-0043
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Research Biopsies in Phase I Clinical Trials: The MD Anderson Cancer Center Experience

Abstract: Background. Research biopsies are crucial for exploring the impact of novel agents on putative targets. The current study assesses the safety and success rate associated with performing such biopsies.Methods. We reviewed the medical records of 155 consecutive patients who had one or more research biopsies as part of a phase I trial from September 2004 to October 2009.Results. Of 281 research biopsies performed, 118 were paired before and after treatment biopsies (total ‫؍‬ 236 biopsies). The most common sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 21 publications
3
54
3
Order By: Relevance
“…This finding is concordant with data from patient surveys [15,16]. It is noteworthy, however, that most studies have suggested research biopsies are safe, with a 0.8%-1.4% major complication rate [4][5][6]17]. For example, of 61 patients who underwent a liver biopsy in a prospective tissue collection study at DFCI, only 1 grade 2 or higher adverse event (grade 2 pain) was noted [7].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is concordant with data from patient surveys [15,16]. It is noteworthy, however, that most studies have suggested research biopsies are safe, with a 0.8%-1.4% major complication rate [4][5][6]17]. For example, of 61 patients who underwent a liver biopsy in a prospective tissue collection study at DFCI, only 1 grade 2 or higher adverse event (grade 2 pain) was noted [7].…”
Section: Discussionsupporting
confidence: 82%
“…The participation rates in research biopsies are highly variable, between 4% and 97% [4][5][6][7]. Although some of this variability can be explained by differences in study design (i.e., whether it is tied to a therapeutic trial, optional or mandatory biopsies, and the number of biopsy time points), undoubtedly, other factors are at work.…”
Section: Introductionmentioning
confidence: 99%
“…Some suggest that mandatory biopsies impact on trial accrual and that when given the choice, patients opt not to have biopsies [15,16]. However, Tabernero et al [17] have reported a 60% acceptance rate for sequential tumor biopsies in a phase I trial, while Rojo et al [18] obtained a 93% acceptance rate in baseline tumor biopsies and 50% acceptance in on-treatment biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…El-Osta and colleagues (11) found that only 4.4% of patients agreed to an optional biopsy when participating in trials, whereas Gomez-Roca and colleagues (12) found that 68% of patients on optional biopsy protocols had at least one biopsy done and 44% had sequential biopsies. …”
Section: Discussionmentioning
confidence: 99%